Characterization and cryopreservation of chironji (Buchanania lanzan) - MALIK, S K; CHOUDHARY, RAVISH; CHAUDHURY, REKHA; KUMAR, SUSHEEL (The Indian Journal of Agricultural Sciences, 2019)
Buchanania lanzan Sperg. (Chironji) is an important underutilized fruit species of north, west and central India. Seventy-four diverse accessions were collected from the diversity rich areas of India. Among the collected accessions, 52 have been characterized for fruit and seed characters. Successful cryopreservation of seed kernel and embryonic axes have been achieved using desiccation followed by fast freezing and air desiccation-freezing method respectively, with high viability up to 85% after cryopreservation. Comprehensive base collection of diverse accessions has been successfully established in the Cryogenebank. Morphological characterization with 20 variables representing 9 qualitative and 11 quantitative characters has been undertaken. All the accessions of B. lanzan were grouped into eight clusters, showing high level of genetic variability within the species. Two-D plot derived from PCA based on first two components showed four major groups, which was found less similar to the clustering pattern of dendrogram. Morphological characters, viz. fruit shape, length, width, colour, pulp colour, stone shape, stone colour; kernel weight and kernel colour represent maximum variability revealed by first three components identified for developing minimal descriptors. Five accessions, viz. IC-552921, IC-552924, IC-546107, IC-546109 and IC-553215 were identified as superior genotypes, which may be further evaluated and utilized as promising accessions for crop improvement.